CONTENT OF LEGAL NORMS’ SANCTIONS IN INFORMATION-PSYCHOLOGICAL APPROACH TO THE RESEARCH OF LEGAL PHENOMENA - A. V. Krasnov (Russian Journal of Economics and Law)
Objective: to reveal the connections between the conventional public values and the content of legal norms’ sanctions by comparative research. Methods: formal-legal, comparative-legal, systemic-structural and axiological. Results: resulting from legislation analysis, as well as other empirical facts, the existence of indirect links between the interests of the modern society and the content of legal norms’ sanctions. These links are most vividly revealed in the sphere of economic crimes and administrative offences, as well as civil-legal delicts. The complex of benefits of the modern society is revealed, which can be subject to influence from legal norms’ sanctions, and their objective conservative character was proved. The efficiency of the search of adequate measures against modern crimes is grounded. Scientific novelty: the complex approach is implemented to the research of the benefits subject to the negative-legal influence, their theoretical-legal structurization is presented; for the first time the direct and indirect links are revealed between the mentioned benefits and public values; the ways of further transformation of legal norms’ sanctions towards increasing their efficiency are specified. Practical value: the provisions formulated as conclusions of the article can be applied in law-making activities for increasing the efficiency of legal norms’ sanctions, which in general will be aimed at improving the law-enforcement in the Russian society.